Stress relief treatment of aluminum/magnesium laminates fabricated by roll bonding technique - Masoud Rashidi; Payam Tayebi; Ramin Hashemi (Heliyon)
Roll bonding of aluminum/magnesium laminates combines the good corrosion resistance of aluminum alloys with the beneficial mechanical properties of magnesium alloys. We studied the microstructure of aluminum Al-1051/AZ31 magnesium laminates fabricated by the roll-bonding process. The fabricated laminates were investigated in the as-fabricated condition and after subsequent stress relief annealing treatment at temperatures ranging from 200 °C to 400 °C. The investigation aims to determine the optimal temperature to decrease the residual stress of the severely deformed microstructure of the roll-bonded Al/Mg laminates. Internal residual stress can limit the application of such laminates. Such a thermal treatment enhances the interdiffusion of Al and Mg at the Al/Mg interface resulting in the formation of intermetallic phases. Intermetallic compounds are undesirable due to their brittleness and impact on the overall laminate structure and integrity. Detailed microstructure characterization of the intermetallic compounds and internal residual stress by means of recrystallization degree revealed that stress-relief treatment at 200 °C/1 h is sufficient to reduce internal residual stress and ensure adequate interdiffusion at Al/Mg interface to minimize the formation of brittle intermetallic compounds in the diffusion zone.